EFFECT OF ADDING NATURAL AND NANO ZINC OXIDE TO THE DITE ON SOME GROWTH PARAMETERS OF CYPRINUS CARPIO L . - Ayat. A. Al-Noori,; A. J. Abuelheni,; M. S. Al-Khshali, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The research aimed to study the effect of natural and nano zinc oxide on some growth parameters of common carp Cyprinus carpio. Seven treatments were used, including the control without any addition, the second, third and fourth treatments by adding nano-zinc oxide at concentrations of 25, 50 and 75 mg/kg feed, respectively, and the fifth, sixth and seventh treatments by adding natural zinc oxide in the same concentrations above. The results showed that the fourth treatment was superior to the traits of the total weight gain, daily growth rate, relative and specific growth rate over the other treatments, which is an indication that the fish benefit from feed enhanced with nanoparticles by 75%, and it differed significantly )p (0.01>from the rest of the treatments. T4 treatment was recorded the best daily growth was 0.29 g/day The best feed conversion ratio was recorded in the same treatment. It can be concluded from the study that the addition of zinc nanoparticles to the diet of fish improves the level of performance and growth without causing any harm to the fish.